2014
DOI: 10.1371/journal.pgen.1004339
|View full text |Cite
|
Sign up to set email alerts
|

Biased, Non-equivalent Gene-Proximal and -Distal Binding Motifs of Orphan Nuclear Receptor TR4 in Primary Human Erythroid Cells

Abstract: We previously reported that TR2 and TR4 orphan nuclear receptors bind to direct repeat (DR) elements in the ε- and γ-globin promoters, and act as molecular anchors for the recruitment of epigenetic corepressors of the multifaceted DRED complex, thereby leading to ε- and γ-globin transcriptional repression during definitive erythropoiesis. Other than the ε- and γ-globin and the GATA1 genes, TR4-regulated target genes in human erythroid cells remain unknown. Here, we identified TR4 binding sites genome-wide usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…To investigate the mechanisms that result in these observed deficiencies in erythroid cell physiology, we compared these results characterizing the murine mutants with previously published human RNA-seq data generated by our laboratory in which CD34 1 cells were induced to undergo erythroid differentiation with or without infection with a lentivirus containing short hairpin RNA (shRNA) against TR4 (shRNA-TR4) or a scrambled control (shRNA-Ctrl, GSE5476). 36 Differentially expressed genes (when compared with shRNA-Ctrl) whose function has been described in erythroid proliferation and differentiation were analyzed as candidate TR4 target genes. 36 shRNA-TR4 in the human erythroid progenitor cells resulted in a 50% to 60% reduction in the abundance of TR4 transcripts (notably without altering TR2 expression; Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the mechanisms that result in these observed deficiencies in erythroid cell physiology, we compared these results characterizing the murine mutants with previously published human RNA-seq data generated by our laboratory in which CD34 1 cells were induced to undergo erythroid differentiation with or without infection with a lentivirus containing short hairpin RNA (shRNA) against TR4 (shRNA-TR4) or a scrambled control (shRNA-Ctrl, GSE5476). 36 Differentially expressed genes (when compared with shRNA-Ctrl) whose function has been described in erythroid proliferation and differentiation were analyzed as candidate TR4 target genes. 36 shRNA-TR4 in the human erythroid progenitor cells resulted in a 50% to 60% reduction in the abundance of TR4 transcripts (notably without altering TR2 expression; Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…36 Differentially expressed genes (when compared with shRNA-Ctrl) whose function has been described in erythroid proliferation and differentiation were analyzed as candidate TR4 target genes. 36 shRNA-TR4 in the human erythroid progenitor cells resulted in a 50% to 60% reduction in the abundance of TR4 transcripts (notably without altering TR2 expression; Figure 6A). As anticipated, one known TR4 direct target gene, 4 human «-globin, exhibited increased expression after TR4 knockdown, although there was no change observed in adult b-globin (b) transcription (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…The association of nuclear receptors with ETS factor motifs in various hematopoietic cells has previously been reported on a genome wide scale for vitamin D receptor and the orphan nuclear receptor TR4 [ 64 , 65 ], but the importance or functionality of this potential cooperation has not been addressed in detail. However, treatment of t(16;21) AML with all-trans retinoic acid (ATRA) has recently been shown to recruit ERG to new genome-wide binding sites, suggesting that the RARa/RXR heterodimer is capable of reprogramming ERG binding.…”
Section: Discussionmentioning
confidence: 99%
“…In erythroid cells, hundreds of genes are repressed (either directly or indirectly) by TR4, while even more genes are activated (58). Analysis of erythroid differentiation in comparative data sets from chromatin immunoprecipitation-sequencing (ChIP-seq) and RNA-seq experiments indicated that the DR motif is more prevalent in the proximal promoters of TR4 direct target genes that are involved in basic biological functions (e.g., mRNA processing, ribosomal assembly, RNA splicing, and primary metabolic processes [58,59]). We also previously identified TRIM28 as an interacting protein of TR2/TR4 (39).…”
Section: The Dred Complex: a Direct ␥-Globin Repressormentioning
confidence: 99%